Preliminary Study About The Application Of Gravicorder For Weight-Shifting and-Bearing Exercise As a New Educational Device of Physiotherapists (International Journal of Physiotherapy, 2023)
Background: To establish an objective evaluation of basic physiotherapy technique, we recorded a mechanical aspect during a lateral weight-shifting (WS) using gravicorder.Methods: Subjects were 18 physiotherapists divided into three groups based on experience year. Our originally developed software converted center of gravity data during WS to 3-dimensional mechanical value.Results: All direction data showed significantly lower in the long experience year group (p